Effectiveness of Basil, Lime, Honey, Candlenut, and Tiwai Onion Herbs Combination as Analgesics and Stamina Stimulator - Andriyanto, Andriyanto; Aurellia, Sharon; Widyanti, Silmy Kamila; Putra, Hamdika Yendri; Widi, Leliana Nugrahaning; Nengsih, Rindy Fazni; Mustik, Aulia Andi; Manalu, Wasmen (Majalah Kedokteran Bandung, 2022)
Traditional medicine is generally considered to be safer than modern medicine because it has lower incidence of side effects and also relatively easy to obtain. The purpose of this study was to examine the analgesic effect of herbs made of basil, lime, honey, candlenut, and Tiwai onions as well as to evaluate the potential of these herbs as a stamina stimulator. This study was conducted at the Laboratory of Animal Management Unit, Faculty of Veterinary Medicine, IPB University, from January–February 2022. Mice were divided into four groups based on the treatment dose with each group consisted of five mice. An analgesic test was conducted using hot water immersion tail-flick test method and the stamina test was performed with swimming endurance test. Data obtained were analyzed using Microsoft Excel 2019 and Minitab 19. Significant differences of the average of each group were shown statistically using the one-way ANOVA and confirmed with Tukey test. Results showed that mice given the combination herbal medicine infusion of with a dose of 4 g/kg body weight had the highest average tail lift time compared to the controls (p<0.05). Mice with a treatment dose of 1 g/kg body weight had the highest analgesic power compared to the other treatment doses. The highest swimming duration was observed in group that received a dose of 1 g/kg body weight. It is concluded that this herbal combination can be used as an analgesic and a stamina stimulator.